Managerial Entrenchment and Capital Structure Decisions. - Berger, Philip G; Ofek, Eli; Yermack, David L (Journal of Finance, 1997)
The authors study associations between managerial entrenchment and firms' capital structures, with results generally suggesting that entrenched CEOs seek to avoid debt. In a cross-sectional analysis, they find that leverage levels are lower when CEOs do not face pressure from either ownership and compensation incentives or active monitoring. In an analysis of leverage changes, the authors find that leverage increases in the aftermath of entrenchment-reducing shocks to managerial security, including unsuccessful tender offers, involuntary CEO replacements, and the addition to the board of major stockholders.